Pengaruh Restrukturisasi Perusahaan Terhadap Kinerja Perusahaan: ( Studi Kasus Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia ) - As’ari, Hasim; Ahmad Pabulo, Azfa Mutiara; Zaman, Badrus (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
This study aims to empirically examine the effect of corporate restructuring on company performance. This analysis uses independent variables, namely debt restructuring, Right issue, Divestment, Acquisition, OPEX and layoffs. The dependent variable is ROA. The sample of this study is the issuer companies that restructured the companies listed on the IDX from 2010 to 2016. The samples of this study were 121 companies selected by purposive sampling method. Statistical methods use Multiple Linear Regression Analysis, by testing the statistical test hypotheses t and Test F. The results of this study conclude that debt restructuring, Right Issue (HMETD), Divestment, Acquisition, OPEX and layoffs significantly positively affect ROA.